Peran Badan Pengelolaan Keuangan Daerah Kabupaten Simeulue dalam Penyusunan Rencana Kerja Pemerintah Daerah - Astuti, Astuti; Husen , Tamitha Intassar (Medan Resource Center, 2023)
This article aims to discuss the Role of the Simeulue Regency Regional Financial Management Agency in the Preparation of Regional Government Work Plans. The Simeulue Regency Regional Financial Management Agency (BPKD) was formed based on the Simeulue Regency Qanun Number 7 of 2007 concerning the implementation of duties, always trying to organize a clean and authoritative government (Good Government) in accordance with the aspirations and expectations of all levels of society. This research is a type of qualitative research. The data in the study were obtained through direct observation and interviews with several informants. The results showed that the BPKD of the Simeulue district played an important role in preparing the local government work plan in the Work Plan and Budget of the Regional Work Unit (RKA-SKPD) of the Regional Financial Management Agency (BPKD) of the Simeulue Regency as a whole in accordance with Permendagri Number 21 of 2011 for the stage of preparing the work plan in the SKPD and the Procedures for preparing the Work Plan and Budget (RKA) in the Simeulue Regency Regional Financial Management Agency for the most part were in accordance with the SOP, and the implementation stage of preparing the RKA had proceeded properly and systematically.